E7 peptide and magnesium oxide-functionalized coaxial fibre membranes enhance the recruitment of bone marrow mesenchymal stem cells and promote bone regeneration - Shengyu Long; Wentong Wang; Yongcheng Chen; Zhihua Wang; Hao Duan; Ping Yuan; Yunrong Xu; Denghui Li; Wan Zhang; Weizhou Wang; Fei He (BMC Biotechnology)
Abstract Background The repair of bone defects remains a significant clinical challenge. Although magnesium (Mg)-based biomimetic scaffolds are widely utilized for bone defect repair, the release of Mg²⁺ ions often leads to an alkaline microenvironment, thereby adversely affecting bone regeneration. Regenerative medicine strategies that leverage the recruitment of endogenous bone marrow mesenchymal stem cells (BMSCs) offer a novel approach to treating bone defects. Methods In this study, we employed poly(L-lactic acid) (PLLA) and polyethylene glycol (PEG) as shell materials and nanomagnesium oxide (nMgO) combined with gelatin (G) as core materials to fabricate coaxial fibre membranes with a “core‒shell” structure via coaxial electrospinning technology. Additionally, we grafted the BMSC-affinitive peptide E7 (EPLQLKM) onto the fibres to achieve specific recruitment of endogenous BMSCs. Results Morphological and structural analyses confirmed the successful formation of the “core‒shell” structure of the fibre membranes. Grafting E7 peptides enhanced the hydrophilicity and mechanical properties of the fibre membranes and maintained pH stability in vitro. In vitro experiments demonstrated that the functionalized fibre membranes significantly promoted BMSC proliferation, migration, and osteogenic differentiation. When implanted into a rat cranial defect model, we observed the formation of new bone tissue and the repair of the bone defect. Conclusions E7 peptide-functionalized coaxial fibre membranes effectively facilitated bone defect repair by promoting the recruitment and osteogenic differentiation of BMSCs, demonstrating substantial potential for tissue engineering applications.